Dossier Imitation - Introduction générale - Odile Petit; Olivier Pascalis (Revue de Primatologie)
This special issue is interested in the ontogeny and the phylogeny of imitation. We have invited experts in developmental psychology and in primatology to discuss the definition of imitation in Human, its existence in non human primate species and to address the question of similarities between the different primate species. Imitation has both a cognitive and a social dimension. Imitation involves, indeed, cognitive processes that are part of social and cultural life. Learning occurs via imitation and several questions can be asked: Is imitation innate? Will studying its ontogeny help understanding its cognitive processes? Finally, is imitation human specific?